The Importance Of The Role Of Optics In The Presence Of Modern Technology In Health Facilities (The Review of Diabetic Studies, 2025)
Background: The role of modern technology is increasing on all the dimensions of present-day healthcare systems and the application and usage of optics is one of the major dimensions. Saudi Arabia is already considering the fild of optics in healthcare sector so as to meet the prevalence of Saudi Vision 2030. Optics in healthcare sector has become very important for timely diagnosis, treatment processes and even supervision of patients. In this present study the researcher had tried to touch all the related dimensions of usage, application, role, and significance of Optics in system of healthcare, that is governed by modern technologies.  Study Objectives: The main objective of the present research is to explore the current level of utilization of optical-techniques for diagnostic imaging, laser-based therapy, and fiber optic based medical communication systems, within the context of the healthcare setting in the country of Saudi Arabia.Materials and Methods: Study is a narrative based review study and uses exploratory research design where the data is gathered from various sources on the basis of pre decieded criteria of inclusion and exclusion. PRISMA is used to segrigate and screen the collected studies. The results are presented in theoritical and chronological manner to give the clear picture of point in question.Results:  This review underscores the need for continued research, capacity building, and strategic planning to ensure that optical innovations benefit all segments of the population and contribute meaningfully to national health security.